PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN MENYUSUN TEKS PROSEDUR SISWA KELAS V SD MUHAMMADIYAH 1 BONTOALA - Mutmainnah; Akib, Tasrif; Akbar, Amal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine how the Discovery Learning model affects students' ability to compose procedural texts. This study was conducted on fifth-grade students at SD Muhammadiyah 1 Bontoala. In this study, a pre-experimental procedure with a One Group Pretest–Posttest Design was used quantitatively. The research sample consisted of 20 students selected through total sampling. Data were collected through pretest and posttest tests as well as observation sheets. With the help of SPSS software, descriptive and inferential statistics, such as paired sample t-tests, were used to evaluate the data. The research results show that the use of the Discovery Learning model improves students' ability to compose procedural texts. The average student score increased from 47.43 in the pretest to 81.27 in the posttest. In addition, 80% of students have met the minimum requirements for completion. The hypothesis test results show a significant difference between students' abilities before and after the treatment, with a significance value of 0.000 (p < 0.05). Observations of students' learning activities during the learning process also fall into the 'good' category. Therefore, it can be concluded that the Discovery Learning model has a significant influence in improving students' ability to compose procedural texts.